2D Ultrasonic Array-based Optical Coherence Elastography - Kang, Haochen (IEEE Trans Ultrason Ferroelectr Freq Control, 2021)
Acoustic radiation force optical coherence elastography (ARF-OCE) has been successfully implemented to characterize the biomechanical properties of soft tissues such as the cornea and the retina with high resolution using single-element ultrasonic transducers for ARF excitation. Most currently proposed OCE techniques, such as air-puff and ARF, have less capability to control the spatiotemporal information of the induced region of deformation, resulting in limited accuracy and low temporal resolution of the shear wave elasticity imaging. In this study, we propose a new method called 2D ultrasonic array-based optical coherence elastography imaging, which combines the advantages of 3D dynamic electronic steering of the 2D ultrasonic array and high-resolution optical coherence tomography (OCT). The 3D steering capability of the 2D array was first validated using a hydrophone. Then, the combined 2D ultrasonic array OCE system was calibrated using a homogenous phantom, followed by an experiment on ex vivo rabbit corneal tissue. The results demonstrate that our newly developed 2D ultrasonic array-based OCE system has the capability to map tissue biomechanical properties accurately, and therefore has the potential to be a vital diagnostic tool in ophthalmology.